Олег Анатольевич Коростелев (11.01.1959—20.03.2020) [In memoriam: Oleg Anatol’evich Korostelev (January 11, 1959 – March 20, 2020)] - Belobrovtseva, Irina; Demidova, Olga (Slavica Revalensia, 2020)
This is a double portrait of a foremost expert in Russian émigré literature, a long-term nauchnyi sotrudnik (research fellow) of the IMLI RAN (A. M. Gorky Institute of World Literature of the Russian Academy of Sciences), and the founding editor of the peer-reviewed journal in Russian literature Literaturnyi fakt, Oleg Korostelev, a friend of both Irina Belobrovtseva and Olga Demidova.